Nutrient composition of cassava flour fortified with pumpkin leaves and its effects on post-prandial blood glucose level among diabetes patients - Balogun, Olanike O.; Olaniran, Olajumoke P.; Oduneye, Motunrayo T. (International Journal Of Community Medicine And Public Health, 2024)
Background: The nutritional and phytochemical content of cassava has shown many health benefits. However, the use of cassava for the control of diabetes and dyslipidemia is poorly researched. Hence this study aims to determine the effect of cassava flour fortified with pumpkin leaves on post-prandial blood glucose level. Methods: The research adopted an experimental study design. The fortified cassava flour was produced at International Institute of Tropical Agriculture, Ibadan, Oyo State, Nigeria. The flour was fortified in the ratio; 90:10 (sample-A), 70:30 (sample-B), and 50:50 (sample-C). The fasting and postprandial plasma of the subjects were taken using Rossmax and Accu Checker. The proximate and micronutrient composition of cassava were analyzed. The data analysis was carried out using the IBM SPSS Statistics, version 25. Results: The result of the post-prandial effect (min/max) of control, sample A, B, and C, was 57/310 mg/dl, 102/282 mg/dl, 79/188 mg/dl, and 74/160 mg/dl respectively. Sample-B had the highest value in ash, protein, and crude fiber contents. Sample-C had the least protein. The control sample had the least fiber content. sample-A had the highest fat content. However, sample-B had the highest percentage of carbohydrate [96.89±0.03 (sample-B), 84.01±0.19 (sample-C), 83.32±0.02 (Control), and 79.35±0.75 (sample-A)]. The micro-nutrient of the control is lower than other samples with the exception of phosphorus. Sample-A had the highest value of potassium, iron, and calcium. Sample-B had the highest value for magnesium and phosphorus. Conclusions: Sample-C had a lowering effect on the post-prandial blood level of the respondents.